2021
DOI: 10.1083/jcb.202109152
|View full text |Cite
|
Sign up to set email alerts
|

Arf6 anchors Cdr2 nodes at the cell cortex to control cell size at division

Abstract: Fission yeast cells prevent mitotic entry until a threshold cell surface area is reached. The protein kinase Cdr2 contributes to this size control system by forming multiprotein nodes that inhibit Wee1 at the medial cell cortex. Cdr2 node anchoring at the cell cortex is not fully understood. Through a genomic screen, we identified the conserved GTPase Arf6 as a component of Cdr2 signaling. Cells lacking Arf6 failed to divide at a threshold surface area and instead shifted to volume-based divisions at increased… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…We started our study by asking how changes to overall cell size impact surface area-based size control. We used wide ( rga4 Δ) and skinny ( rga2 Δ) mutants to uncouple the scaling of cell surface area, volume, and length, similar to previous work (Figure 1B) (Pan et al, 2014; Facchetti et al, 2019; Opalko et al, 2022). We designed a semi-automated image analysis pipeline to measure cell geometry (Figure S1A), which confirmed that wild type cells divide at a constant surface area while cdr2 Δ cells divide at a constant volume (Figures S1B-S1E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We started our study by asking how changes to overall cell size impact surface area-based size control. We used wide ( rga4 Δ) and skinny ( rga2 Δ) mutants to uncouple the scaling of cell surface area, volume, and length, similar to previous work (Figure 1B) (Pan et al, 2014; Facchetti et al, 2019; Opalko et al, 2022). We designed a semi-automated image analysis pipeline to measure cell geometry (Figure S1A), which confirmed that wild type cells divide at a constant surface area while cdr2 Δ cells divide at a constant volume (Figures S1B-S1E).…”
Section: Resultsmentioning
confidence: 99%
“…Fission yeast cells were grown at 25°C in YE4S medium to logarithmic phase for imaging as previously described (Opalko et al, 2022). Cells were placed in a coverglass-bottom dish (P35G-1.5-20C; MatTek), and covered with a piece of YE4S agar prewarmed to 25°C.…”
Section: Analysis Of Cell Geometry and Fluorescent Protein Intensity ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this working model, we sought additional information about these Cdr2 cytoplasmic clusters. Cdr2 recruits Cdr1 kinase, Arf6 GTPase, and anillin-like Mid1 to cortical nodes ( 17 , 18 , 29 , 30 ). We did not observe strong recruitment of either Cdr1 or Arf6 to cytoplasmic clusters in P Tet -cdr2 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this working model, we sought additional information about these Cdr2 cytoplasmic clusters. Cdr2 recruits Cdr1 kinase and Arf6 GTPase to cortical nodes (Martin and Berthelot-Grosjean, 2009; Moseley et al ., 2009; Opalko et al ., 2022), but we did not observe strong recruitment of either Cdr1 or Arf6 to cytoplasmic clusters in P Tet -cdr2 cells (Figure 4A-B). Thus, Cdr2 and Wee1 might be the primary components of these clusters.…”
Section: Resultsmentioning
confidence: 99%